1984
DOI: 10.3354/meps017237
|View full text |Cite
|
Sign up to set email alerts
|

Temperature response of photosynthetic capacity and carboxylase activity in Arctic marine phytoplankton

Abstract: The temperature response of photosynthetic capacity was compared to that of 3 carboxylating enzymes in Arctic marine phytoplankton. Only the activity of ribulose-1.5-bisphosphate carboxylase (RuBPC) consistently exhibited an apparent activation energy equivalent to that of photosynthetic capacity. This is the first indication from field samples of phytoplankton that changes in the activity of RuBPC may be closely associated with changes in photosynthetic capacity. The maximum photosynthetic capacity attained b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 20 publications
1
58
2
Order By: Relevance
“…This is consistent with previous studies of the region (Carmack et al 2006;Tremblay et al 2008;Lee et al 2010), which suggested that P-E parameters in the ice-associated region of the Chukchi Sea vary primarily based on nutrients, because shade-adapted phytoplankton can utilize light at much lower levels than can their high-light adapted counterparts. However, our results do not as closely support the temperature-and light-control theory of some earlier studies of the region (Li et al 1984;Harrison and Platt 1986;Harrison and Cota 1991), hinting at the possibility that recent changes in sea ice and environmental conditions may be altering phytoplankton growth and photosynthesis in several fundamental and important ways, and/or that the data sets are not as comparable as we are assuming in this study (e.g., possibly because of biases in sampling location, timing, methodology, etc.). More work is needed to fully understand the effects of changing environmental conditions on P-E parameters of natural phytoplankton populations from this dynamic region.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…This is consistent with previous studies of the region (Carmack et al 2006;Tremblay et al 2008;Lee et al 2010), which suggested that P-E parameters in the ice-associated region of the Chukchi Sea vary primarily based on nutrients, because shade-adapted phytoplankton can utilize light at much lower levels than can their high-light adapted counterparts. However, our results do not as closely support the temperature-and light-control theory of some earlier studies of the region (Li et al 1984;Harrison and Platt 1986;Harrison and Cota 1991), hinting at the possibility that recent changes in sea ice and environmental conditions may be altering phytoplankton growth and photosynthesis in several fundamental and important ways, and/or that the data sets are not as comparable as we are assuming in this study (e.g., possibly because of biases in sampling location, timing, methodology, etc.). More work is needed to fully understand the effects of changing environmental conditions on P-E parameters of natural phytoplankton populations from this dynamic region.…”
Section: Discussioncontrasting
confidence: 56%
“…This is contrary to what would be expected if temperatures controlled primary productivity through the regulation of enzymatic activity (Li et al 1984). Although the regression analysis does show that temperature was a key factor in the prediction of five of the eight parameters analyzed, we suggest that the importance of the temperature term was exaggerated because of its tendency toward co-variation with both light (positively correlated) and nutrient concentration (inversely correlated).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…For example, cyanobacteria may adjust their photosynthetic apparatus in order to acclimate to the prevailing temperature. They tend to have decreased photosynthetic capacity (P max ) at low temperatures due to depressed activity of ribulose-1,5-bisphosphate carboxylase (Rubisco) (Li et al, 1984 ;Raven & Geider, 1988). Therefore, a potential adaptive strategy for polar cyanobacteria would be to decrease their concentrations of chlorophyll a and light harvesting pigments (Geider, 1987 ;Davison, 1991) while increasing the activity of Rubisco (Li & Morris, 1982).…”
Section: mentioning
confidence: 99%